Desenvolvimento de plano terapêutico utilizando estimulação transcraniana por corrente contínua para neuromodulação do zumbido - Cunha, Germanda Maria Soares da (2020)
Introduction: Tinnitus is a phantom sound sensation experienced in the absence of any external sound source, which has a significant impact on quality of life. It affects both sexes equally, occurring most often between 40 and 70 years of age. Method: The study is characterized as a controlled placebo clinical trial, which included 31 patients with chronic tinnitus, seen at a private clinic (Nucleus for Integrated Health) in partnership with the Human Motricity and Neuroscience Laboratory (LAMHNEC) linked to the Post-Graduation in Health Science and Technology from the Nucleus of Strategic Technologies in Health - NUTES of UEPB. The study was approved by the Research Ethics Committee (CAAE: 21613019.0.0000.5187). Participants of both sexes, aged over 18 years were divided into two groups (tDCS and sham). The collection and therapy procedures consisted of audiological evaluation, with audiometry and acuphenometry tests, in addition to the self-assessment questionnaires for tinnitus - Tinnitus Handicap Inventory (THI), Visual Analog Scale (VAS), and the Inventory of State-Trait Anxiety (IDATE). After the interviews, an intervention with the tDCS was initiated, which had weekly consultations. Results: Descriptive statistics of the variables were performed: age, sex, laterality, hearing loss and type of sound, using Pearson's chi-square test and no significant differences were observed between groups, that is, in these constructs the sample was homogeneous. Regarding the left ear, the analysis between sessions showed that for tDCS treatment there was an average increase in intensity from 8 dB to 10 dB, while for the sham group there was an average decrease in intensity of 8 dB and to 6 dB. Thus, in the sham group, there was an improvement in the sound sensation of intensity in both ears. Transcranial Direct Current Stimulation can be an alternative of great value and efficiency, due to its prominence due to the practicality and simplicity in the application, safety, low cost and satisfactory results in relation to suppression and / or reduction of discomfort caused by tinnitus. A better result of positive effects and presence of symptom relief was observed when the following parameters were combined: anodic TCC in the Left Temporoparietal Area - TTA or bilateral Dorsolateral Pre-Frontal Cortex - CPFDL (with anode on the right and cathode on the left), 5 sessions, application of 20 minutes with a current of 2 mA of intensity. In the present study, the active group showed significantly reduced scores for the measurement of auditory discomfort, intensity and frequency, improving the sensation of discomfort. Conclusion: Transcranial direct current stimulation was able to modulate sound perception in relation to the symptom's psychoacoustic characteristics (sensation of intensity, sensation of frequency and type of sound), in addition to reducing the auditory discomfort caused by it. The results were not very expressive, but given the reports and figures found, the technique was also effective in reducing the discomfort caused by the symptom.